Microsaccades reflect the dynamics of misdirected attention in magic - Anthony S. Barnhart; Francisco M. Costela; Susana Martinez-Conde; Stephen L. Macknik; Stephen D. Goldinger (Bern Open Publishing, 2019)
The methods of magicians provide powerful tools for enhancing the ecological validity of laboratory studies of attention. The current research borrows a technique from magic to explore the relationship between microsaccades and covert attention under near-natural viewing conditions. We monitored participants' eye movements as they viewed a magic trick where a coin placed beneath a napkin vanishes and reappears beneath another napkin. Many participants fail to see the coin move from one location to the other the first time around, thanks to the magician's misdirection. However, previous research was unable to distinguish whether or not participants were fooled based on their eye movements. Here, we set out to determine if microsaccades may provide a window into the efficacy of the magician's misdirection. In a multi-trial setting, participants monitored the location of the coin (which changed positions in half of the trials), while engaging in a delayed match-to-sample task at a different spatial location. Microsaccades onset times varied with task difficulty, and microsaccade directions indexed the locus of covert attention. Our com-bined results indicate that microsaccades may be a useful metric of covert attentional processes in applied and ecologically valid settings.